2008
DOI: 10.1136/bjo.2007.131680
|View full text |Cite
|
Sign up to set email alerts
|

Sources of patient knowledge and financing of cataract surgery in rural China: the Sanrao Study of Cataract Outcomes and Up-Take of Services (SCOUTS), Report 6

Abstract: Strategies to increase uptake of cataract surgery in rural China may benefit from enhancing word-of-mouth advertising (such as with pseudophakic motivators), using television advertising where affordable, and micro-credit or other programmes to enable patients to pay their own fees, thus increasing uptake of second-eye surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Besides self‐reported VF and QOL, there are other indices of patient satisfaction that are of importance to cataract surgical programmes. Recent evidence suggests that positive word of mouth advertising is of particular importance in patients' willingness to accept surgical services in rural Asia 20 . In the current study, 90% of patients were not only satisfied with their own surgery, but would recommend it to others.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Besides self‐reported VF and QOL, there are other indices of patient satisfaction that are of importance to cataract surgical programmes. Recent evidence suggests that positive word of mouth advertising is of particular importance in patients' willingness to accept surgical services in rural Asia 20 . In the current study, 90% of patients were not only satisfied with their own surgery, but would recommend it to others.…”
Section: Discussionmentioning
confidence: 47%
“…Recent evidence suggests that positive word of mouth advertising is of particular importance in patients' willingness to accept surgical services in rural Asia. 20 In the current study, 90% of patients were not only satisfied with their own surgery, but would recommend it to others. Given the relatively high proportion of persons with poor postoperative results, the high levels of self-reported satisfaction may reflect poor preoperative vision (which we were unable to assess).…”
Section: Discussionmentioning
confidence: 58%
“…Considering actual uptake of services, Nd:YAG capsulotomy improved VA to ⩾6/18 in 9% (3/35) of eyes and refraction in 26% (9/35) of eyes with presenting VA <6/18. Despite the high uptake of YAG and the previously reported low uptake of refractive services28 in the SCOUTS cohort, the effective yield in terms of the proportion of patients with poor presenting vision whose VA was improved with refraction was higher than that for YAG capsulotomy.…”
Section: Resultsmentioning
confidence: 69%
“…The social set-up in rural China is such that the elderly are dependent on the younger generation for fulfillment of their financial needs. Other studies 22,28 have also found that elderly cataract patients are frequently dependent on their family to provide full or partial support for surgery in rural China. Therefore, it is important to educate the whole family about the visual needs of the elderly with an emphasis on the need for family support during any future cataract screening programs.…”
Section: Other Reasonsmentioning
confidence: 93%